Why Do Firms Issue Convertible Bonds with a High Initial Conversion Premium? - Kaźmierczak, Damian (Acta Universitatis Lodziensis. Folia Oeconomica, 2018)
This paper identifies the motives for selling convertible bonds with a higher‑than‑average initial conversion premium, using a sample of 300 convertible debt issues carried out between 2004 and 2014 by manufacturing and service companies from the United States, Europe and Asia. Empirical analysis indicates that high premium convertibles are issued by strongly undervalued companies with poor financial performance, looking to increase their equity capital through the backdoor, under more favorable conditions in comparison to the issuance of common stock. For this reason, convertibles designed in this way are likely to be perceived by firms as a delayed equity rather than a debt sweetener.